2013
DOI: 10.3390/ijms140917781
|View full text |Cite
|
Sign up to set email alerts
|

Green Leaf Volatiles: A Plant’s Multifunctional Weapon against Herbivores and Pathogens

Abstract: Plants cannot avoid being attacked by an almost infinite number of microorganisms and insects. Consequently, they arm themselves with molecular weapons against their attackers. Plant defense responses are the result of a complex signaling network, in which the hormones jasmonic acid (JA), salicylic acid (SA) and ethylene (ET) are the usual suspects under the magnifying glass when researchers investigate host-pest interactions. However, Green Leaf Volatiles (GLVs), C6 molecules, which are very quickly produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
319
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(333 citation statements)
references
References 210 publications
(286 reference statements)
5
319
1
8
Order By: Relevance
“…In the present study, nonanal was found to inhibit mycelial growth of Botrytis cinerea in varying degrees, with the MIC and MFC values 100 and 160 μL/L, respectively (Figure 1). These results confirmed the antifungal activity of nonanal previously found at relatively high concentrations [42]. Further, our results indicated that nonanal could damage the plasma membrane of spores (Figure 2).…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, nonanal was found to inhibit mycelial growth of Botrytis cinerea in varying degrees, with the MIC and MFC values 100 and 160 μL/L, respectively (Figure 1). These results confirmed the antifungal activity of nonanal previously found at relatively high concentrations [42]. Further, our results indicated that nonanal could damage the plasma membrane of spores (Figure 2).…”
Section: Discussionsupporting
confidence: 80%
“…GLVs are C 6 molecules which are produced and emitted rapidly following herbivory or pathogen infection by almost every green plant (Scala et al, 2013). Mechanical damage of plant tissues can result in both quantitative and qualitative changes in the volatile emissions of GLVs (Scala et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As for the other BVOCs the highest concentrations 15 of most alcohols and acetates were measured in summer. Most of the measured alcohols and acetates were GLVs, which are emitted due to herbivory or pathogen infection by almost every green plant (Scala et al 2013) or due to physical damage of plants (Hakola et al 2001). …”
Section: Concentrations Of Alcohols and Acetatesmentioning
confidence: 99%